Konsep Pendekatan Gender Aware Counseling Berbasis Islam untuk Meminimalisir Aksi Radikalisme di Kalangan Perempuan Melalui Pemahaman Peran Gender - Nadhifatuz Zulfa (IQTIDA : Journal of Da'wah and Communication, 2021)
This article was written because of the radicalism that is taking place in Indonesia and involving women as one of the perpetrators. The role of women is now no longer a follower, supporter, or provocateurs in the act of radicalism in Indonesia, but even more extreme is the martyr "bride" suicide bombing. One of the causes is inequality and misunderstanding of understanding gender roles. This requires intervention efforts as well as prevention so that no similar actions will occur in the future. One of these efforts is through gender-based counseling services by inserting Islamic values ​​into their services to female clients (Gender Aware Counseling / GAC based on Islam). The purpose of writing this article is to understand the description of GAC based on Islam in minimizing radicalism among women through understanding gender roles based on the Qur'an and Hadith. The GAC technique used includes the conceptualization of gender and radicalism role problems, counseling interventions, and termination. The research method used is qualitative description research. It is expected that using Islamic-based GAC can minimize radicalism in Indonesia, especially those carried out by women